Maternal and offspring behavior in free‐ranging Japanese and moor macaques: A comparative approach. Issue 2 (27th December 2022) - Castellano‐Navarro, Alba; Beltrán Francés, Víctor; Albiach‐Serrano, Anna; MacIntosh, Andrew J. J.; Illa Maulany, Risma; Ngakan, Putu O.; Liebal, Katja; Amici, Federica
Abstract: Female primates represent the most important social partner for their developing offspring. However, mothers may strongly differ in the way they relate to their offspring (e.g., in terms of two different dimensions: protectiveness and rejection). In this study, we aimed to assess how dominance style predicts (i) changes in maternal behavior through offspring development, and (ii) the link between maternal behavior and offspring behavior. We conducted behavioral observations on 34 free‐ranging immatures of two species of macaques with different dominance styles: less tolerant Japanese macaques (JM;  Macaca fuscata ) and more tolerant moor macaques (MM;  Macaca maura ). Our results showed that maternal behavior differed between JM and MM: maternal proximity and grooming decreased through offspring development more quickly in MM than in JM, whereas maternal rejection and aggression, which were generally more frequent in JM, decreased with offspring age similarly in both species. In contrast, maternal restraint of offspring decreased similarly with offspring age in both species. Furthermore, dominance style was differentially associated with the link between maternal and offspring behavior: in MM only, maternal grooming predicted an increase of the probability that offspring interacted with partners other than their mothers and engaged in solitary play, whereas maternal rejection predicted a decrease in the occurrence of solitary play. Overall, these results suggest interspecific variation in maternal behavior during offspring's first years of life, and point to the possibility that these differences may have an important role in shaping their behavioral development. Abstract : Summary of the results obtained in the current study, which compares maternal and offspring behavior in free‐ranging Japanese and moor macaques. Below the images are the differences we have found between the two species and between the images are the similarities between them. The plus symbol represents "more frequent, " up arrows represent "increase, " and down arrows represent "decrease." Highlights: Maternal protectiveness decreased with offspring age generally more quickly in moor macaques (MM) than in Japanese macaques (JM). Maternal rejection was more frequent in JM than in MM. In MM, higher maternal grooming and lower rejection were linked to more social and playful offspring. In JM, maternal grooming was linked to less social and playful offspring.